Traffic Optimization Through Waiting Prediction and Evolutive Algorithms. - García, Francisco; Hernández, Helena; Moreno García, María N.; F. De Paz, Juan; F. López, Vivian; Bajo, Javier (International Journal of Interactive Multimedia and Artificial Intelligence, 2025)
Traffic optimization systems require optimization procedures to optimize traffic light timing settings in order to improve pedestrian and vehicle mobility. Traffic simulators allow obtaining accurate estimates of traffic behavior by applying different timing configurations, but require considerable computational time to perform validation tests. For this reason, this project proposes the development of traffic optimizations based on the estimation of vehicle waiting times through the use of different prediction techniques and the use of this estimation to subsequently apply evolutionary algorithms that allow the optimizations to be carried out. The combination of these two techniques leads to a considerable reduction in calculation time, which makes it possible to apply this system at runtime. The tests have been carried out on a real traffic junction on which different traffic volumes have been applied to analyze the performance of the system.